20 years of work on Marine Recreational Fisheries at the Thünen Institute of Baltic Sea Fisheries - Marc Simon Weltersbach; Wolf-Christian Lewin; Kevin Haase; Josefa Eckardt; Harry Vincent Strehlow (Johann Heinrich von Thünen-Institut, 2024)
Following the advice of the 2014 evaluation of the Thünen Institute by the German Science and Humanities Council, the Thünen Institute has started to encourage its working groups to be evaluated by external experts as part of its quality management. The Marine Recreational Fisheries Working Group of the Thünen Institute of Baltic Sea Fisheries was selected to undergo this evaluation process. Two external scientific experts on recreational fisheries, Dr. Kieran Hyder (CEFAS, UK) and Prof. Dr. Warren Potts (Rhodes University, SA) were requested to evaluate the working group based on the following terms of references: (i) Quality assessment and technical evaluation of the recreational fisheries survey and monitoring programme run by the working group; (ii) Evaluation of the scientific excellence in terms of methods used, technical expertise of the staff and scientific and popular science outputs; (iii) Evaluation of research priorities with focus on their effectiveness and usefulness for the advisory competence of the Thünen institute; (iv) Evaluation of national and international research collaborations and participation in national and international scientific committees and advisory boards. The evaluation was conducted as a face-to-face workshop at the Thünen Institute of Baltic Sea Fisheries in Rostock, Germany in November 2022. This report served to familiarize the evaluators with the Thünen Institute and the work of the Marine Recreational Fisheries Working Group in the past 20 years. It contains detailed information on the genesis and development of the working group, the research and monitoring activities, the technical expertise of the group members, the scientific and popular science results, the advisory competencies and the national and international networking of the group. The evaluation was concluded with a summary statement by the two evaluators (see Appendix 2), which includes an assessment of the current work and recommendations for future areas of development. – – Auf Grundlage einer Empfehlung des Deutschen Wissenschaftsrats nach der Evaluierung des Thünen-Instituts im Jahr 2014 hat das Thünen-Institut damit begonnen, seine Arbeitsgruppen im Rahmen des Qualitätsmanagements durch externe Fachleute evaluieren zu lassen. Die Arbeitsgruppe (AG) "Marine Freizeitfischerei" des Thünen-Instituts für Ostseefischerei wurde ausgewählt, um sich diesem Evaluierungsprozess zu unterziehen. Zwei externe wissenschaftliche Fachleute für Freizeitfischereiforschung, Dr. Kieran Hyder (CEFAS, UK) und Prof. Dr. Warren Potts (Rhodes University, SA), wurden gebeten, die Arbeitsgruppe auf der Grundlage der folgenden Vorgaben zu evaluieren: (i) Qualitätsbewertung und fachliche Evaluierung des von der Arbeitsgruppe durchgeführten Survey- und Monitoringprogramms für die marine Freizeitfischerei in Deutschland; (ii) Bewertung der wissenschaftlichen Exzellenz in Bezug auf die angewandten Methoden, die fachliche Kompetenz der Mitarbeitenden und die wissenschaftlichen und populärwissenschaftlichen Produkte; (iii) Evaluierung von Forschungsschwerpunkten mit Fokus auf deren Effektivität und Nützlichkeit hinsichtlich der Beratungskompetenz des Thünen-Instituts; (iv) Bewertung der nationalen und internationalen Forschungskooperationen und der Mitarbeit in nationalen und internationalen wissenschaftlichen Gremien und Beiräten. Die Evaluation wurde in Form eines Workshops am Thünen-Institut für Ostseefischerei in Rostock im November 2022 durchgeführt. Dieser Bericht diente dazu, die Gutachter mit dem Thünen-Institut und der Arbeit der AG "Marine Freizeitfischerei" in den vergangenen 20 Jahren vertraut zu machen. Er enthält detaillierte Informationen über die Entstehung und Entwicklung der AG, die Forschungs- und Monitoringaktivitäten, die fachliche Expertise der Gruppenmitglieder, die wissenschaftlichen und populärwissenschaftlichen Ergebnisse, die Beratungskompetenzen sowie die nationale und internationale Vernetzung der Gruppe. Die Evaluation wurde mit einer zusammenfassenden Beurteilung der beiden Gutachter abgeschlossen (siehe Appendix 2), die eine Bewertung der aktuellen Arbeiten und Empfehlungen für künftige Entwicklungsbereiche enthält.
urn:nbn:de:gbv:253-202403-dn067789-4
Keywords: 630; angling; cod; evaluation; marine recreational fisheries working group; recreational fishing; research; survey methods; Thünen Institute of Baltic Sea Fisheries; Angeln; Dorsch; Evaluation; Forschung; Marine Freizeitfischerei; Survey-Methoden; Thünen-Institut für Ostseefischerei